Association between thermal threshold abnormalities and peripheral artery disease in patients with type 2 diabetes - Sheen, Yi-Jing (Medicine (Baltimore), 2018)
Both diabetic peripheral neuropathy and peripheral arterial disease (PAD) cause foot ulcers and often result in non-traumatic amputations in patients with type 2 diabetes. This study aimed to evaluate the association between clinical variables, PAD, and subclinical diabetic small fiber peripheral neuropathy detected by abnormal thermal thresholds of the lower extremities in patients with type 2 diabetes. We investigated 725 consecutive patients with type 2 diabetes (male/female: 372/353; mean age, 67 ± 11 years) who did not have apparent cardiovascular disease (including coronary artery disease, arrhythmia, and stroke) and who underwent the quantitative sensory test for thermal (warm and cold) thresholds of the lower limbs and ankle-brachial index (ABI)/toe-brachial index (TBI) examinations in 2015. The analyses included glycated hemoglobin, estimated glomerular filtration rate, and other characteristics. In total, 539 (74.3%) patients showed an abnormality of at least 1 thermal threshold in their feet. All patients with an abnormal ABI (<0.9) had concurrent impaired thermal thresholds, and 93% (87/94) of patients with an abnormal TBI experienced abnormal thermal thresholds in the lower limbs. Age- and sex-adjusted TBI and estimated glomerular filtration rate were significantly correlated to abnormal thermal thresholds. In the multivariate analysis, fasting plasma glucose, and glycated hemoglobin were independently associated with abnormal thermal thresholds in the lower extremities. Subclinical thermal threshold abnormalities of the feet are significantly associated with PAD and nephropathy in patients who have type 2 diabetes without cardiovascular disease.